High-efficiency overall alkaline seawater splitting: using a nickel–iron sulfide nanosheet array as a bifunctional electrocatalyst. Issue 3 (5th January 2023) - Chen, Jie; Zhang, Longcheng; Li, Jun; He, Xun; Zheng, Yinyuan; Sun, Shengjun; Fang, Xiaodong; Zheng, Dongdong; Luo, Yongsong; Wang, Yan; Zhang, Jing; Xie, Lisi; et al.
Abstract : NiFeS nanosheet array on Ni foam (NiFeS/NF) behaves as a superb bifunctional electrocatalyst for overall seawater splitting, attaining a commercially demanded current density of 500 mA cm −2 at a low cell voltage of 1.85 V with robust stability. Abstract : The use of large-current-density electrolysis of seawater is promising for a massive hydrogen (H2 ) production. This process, however, requires high-performance and cost-effective bifunctional catalysts for the oxygen evolution reaction (OER) and the hydrogen evolution reaction (HER). Herein, a nickel–iron sulfide nanosheet array on nickel foam (NiFeS/NF) is demonstrated to be a superb bifunctional electrocatalyst for seawater splitting, delivering the industrially demanded current density of 500 mA cm −2 at overpotentials of 300 and 347 mV for OER and HER in alkaline seawater, respectively. Moreover, its corresponding two-electrode electrolyzer only requires a cell voltage of 1.85 V to drive 500 mA cm −2 and shows a strong stability for at least 50 h of electrolysis in alkaline seawater, outperforming the most recently reported seawater-splitting catalyst electrodes.